Assessment of Soil Quality Index Based on Chemical Properties at Various Land Use and Criticality Levels - Diva Nuri Latifah; Maroeto Maroeto; Purwadi Purwadi (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Land damage will reduce the quality of land function and increase the area of critical land. Land use in the Manten Subwatershed cause changes land function that have the potential to increase the criticality level of a land. This study aims to measure the soil quality index from the chemical aspect of critical land in the Manten Subwatershed. Surveys at sampling points were conducted on three types of land use (kaleyard, rice fields, and dry fields) combined with three levels of critical conditions (not critical, critical, and potentially critical). Each combination was carried out at three locations, involving 27 sampling points. Soil quality indicators measured in terms of chemistry include soil pH, nitrogen, phosphorus, potassium, and soil organic matter content. The results of the study showed that all sampling points had a very low soil quality index with an SQI score between 0.06 and 0.122 and an average pH that tended to be low (<6), N-total content of 0.137%-0.308%, phosphorus of 70.97-655.66 ppm, exchangeable potassium of 0.490-2.690 me/100 g, and organic matter 0.023%-0.044%. The practice of adding organic matter needs to be implemented to improve soil quality. Keywords: Critical Land, Land Use, Chemical Properties, Soil Quality Index, Sub Watershed.